Personalidad y motivación: entornos humanos y programación pulsional del constructo psíquico - Maurial Chávez, Iván (2011)
The present article mentions the motivation subject from the multidimensional comprehension by P. Lersch which prevents of any reductionism of the psychic life, connecting it in relation to a philosophy of mind. For such fact, it will be necessary to provide a global idea of the psychological strata and to reflect considering the subject of the endothymic lifestyle, particularly in the pulsion experiences related to life (vitality) of the appropriation (Me as an individual) and the “we-ness” (transitivity). The underlying subject is the image of the man as a biologic being, who being capable to transmit culture, changes since the animality to the value world well as the transcendent sense as the specific motivation of the human being.